2016
DOI: 10.3758/s13421-016-0612-0
|View full text |Cite
|
Sign up to set email alerts
|

Thinking about a limited future enhances the positivity of younger and older adults’ recall: Support for socioemotional selectivity theory

Abstract: Compared with younger adults, older adults have a relative preference to attend to and remember positive over negative information. This is known as the “positivity effect,” and researchers have typically evoked socioemotional selectivity theory to explain it. According to socioemotional selectivity theory, as people get older they begin to perceive their time left in life as more limited. These reduced time horizons prompt older adults to prioritize achieving emotional gratification and thus exhibit increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 46 publications
(60 reference statements)
3
63
0
3
Order By: Relevance
“…And recently, Barber et al . [30] demonstrated that the positivity effect can be effectively produced in younger people by experimentally limiting future time horizons.…”
Section: Socioemotional Selectivity Theorymentioning
confidence: 99%
“…And recently, Barber et al . [30] demonstrated that the positivity effect can be effectively produced in younger people by experimentally limiting future time horizons.…”
Section: Socioemotional Selectivity Theorymentioning
confidence: 99%
“…Thus, manipulations of time perspective provide a cleaner way to examine if there is a relationship between time perspective and the positivity effect. Indeed, studies manipulating time perspective have shown that shifting to a more limited time perspective increases positivity in emotion perception (Kellough and Knight, 2012) and memory (Barber et al, 2015). …”
Section: Relations Between Emotional Processing In Aging and Brain Fumentioning
confidence: 99%
“…When older adults were asked to imagine that their life span would be extended 20 additional years, for example, their social partner preference mirrored those of their younger counterparts. Conversely, when younger adults had a shortened time perspective, such as in studies where they were asked to imagine that they were moving away from their current social circle, or where asked to imagine having an illness with a poor prognosis or simply thinking about a more limited future, their partner selection and emotional experience were similar to those of healthy older adults (e.g., Barber et al 2016).…”
Section: Key Research Findingsmentioning
confidence: 99%